A novel biosenser for hydrogen peroxide based on horseradish peroxidase immobilised on a zinc oxide-multiwalled carbon nanotube composite. - Nyawo, Bonita C. (Midlands State University, 2017)
A novel biosensor for hydrogen peroxide was constructed based on the immobilization of horseradish peroxidase on zinc oxide-multiwalled carbon nanotubes matrix. The model redox enzyme, horseradish peroxidase (HRP) was physically (physical adsorption) immobilized on the ZnO/MWCNT modified electrode surface. UV-Visible spectra of HRP and HRP/ZnO/MWCNT displayed soret bands at 407 and 390 nm, respectively and thus the immobilised HRP retains its native structure. The modified electrode was characterised by cyclic voltammetry and electrochemical impedance in a redox probe. The surface area of the electrode after modification was 0.123cm2, which was almost twice as that of a bare glassy carbon. The fabricated sensor was applied for the detection of hydrogen peroxide. The LOD and LOQ were found to be 3.48 × 10-7 M and 1.05 × 10-6M, respectively. The sensor displayed good reproducibility and stability for the detection of hydrogen peroxide.